Carbon Pricing as a Tool for Cross-Border Carbon Regulation and “Green” Transformation of the Global Economy - M. V. Lysunets (Мир новой экономики, 2023)
The relevance of the study stems from the need to establish a mechanism for cross-border carbon regulation in the global economy.The subject of the study is different systems of carbon pricing in international practice in order to reduce greenhouse gas emissions.The purpose of the work is to analyse the current state of decarbonisation of the economy and energy transition as well as the challenges, taking into account current trends in the world economy; to identify the existing problems in the further development of transboundary carbon regulation. Using data from official Russian and foreign sources one can examine specific features and shortcomings of the major existing systems of carbon regulation in international practice, one can also analyse carbon charges in major countries and regions of the world from the perspective of sufficiency for meeting carbon neutrality targets by 2050.The study is based on a comprehensive approach to the consideration of possible options for the development of international carbon regulation and pricing. In the course of the research, the authors identify the existing problems in the decarbonisation of the world economy; study the objectives and possible consequences of the introduction of a carbon tax in the European region in 2026; and study the scenarios for the further development of the Russian economy as part of the global energy transition as set out in the Strategy for Socio-Economic Development of the Russian Federation. The main directions for the development of Russia’s regional system of international carbon units trade were also outlined and the prospects for this system integration into the international emissions trading system were assessed.